If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -8) = (2x + 5)(x + -6) Reorder the terms: x(-8 + 2x) = (2x + 5)(x + -6) (-8 * x + 2x * x) = (2x + 5)(x + -6) (-8x + 2x2) = (2x + 5)(x + -6) Reorder the terms: -8x + 2x2 = (5 + 2x)(x + -6) Reorder the terms: -8x + 2x2 = (5 + 2x)(-6 + x) Multiply (5 + 2x) * (-6 + x) -8x + 2x2 = (5(-6 + x) + 2x * (-6 + x)) -8x + 2x2 = ((-6 * 5 + x * 5) + 2x * (-6 + x)) -8x + 2x2 = ((-30 + 5x) + 2x * (-6 + x)) -8x + 2x2 = (-30 + 5x + (-6 * 2x + x * 2x)) -8x + 2x2 = (-30 + 5x + (-12x + 2x2)) Combine like terms: 5x + -12x = -7x -8x + 2x2 = (-30 + -7x + 2x2) Add '-2x2' to each side of the equation. -8x + 2x2 + -2x2 = -30 + -7x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -8x + 0 = -30 + -7x + 2x2 + -2x2 -8x = -30 + -7x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -8x = -30 + -7x + 0 -8x = -30 + -7x Solving -8x = -30 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -8x + 7x = -30 + -7x + 7x Combine like terms: -8x + 7x = -1x -1x = -30 + -7x + 7x Combine like terms: -7x + 7x = 0 -1x = -30 + 0 -1x = -30 Divide each side by '-1'. x = 30 Simplifying x = 30
| 6y=-17 | | (4x+34)+(7x-10)+(5x+12)=180 | | v^2-3v-40=0 | | 60(10-x)=90 | | 10-3/4x=5 | | -37=-11.9t-4.9t^2 | | 2x-(4x-1)=9 | | x+1+9=3x-24 | | 4.9t^2-125-5.2t=0 | | -2x-13=3x+12 | | 7x+19= | | x+1+9=3-24 | | 5x^4-3x^3-3x^2=0 | | 4-x+2=3x+5 | | 4r-4/8=4r-8/4 | | 46-9x=18+5x | | x/a-5+b | | 6(-7x+3)+2x=1 | | 5y+5.2=2-5y | | (-10*-2)+(2*6)/-2 | | x/3+26=14 | | 5y^2-9x^2-36=0 | | -1=-1.6+-0.8m | | 7*r-7/2 | | x+x+(x+61.5)=180 | | 4(5-3x)= | | -3x=-14+4x | | 8x-52=6x+8 | | -2/3x+53+59 | | 8h+9k-9(8h-9k)= | | 3(2x-5)=6(2+x)+4 | | 21/3x+2=27/3x |